KUALITAS PERKAWINAN PADA PASANGAN USIA DINI : : Analisis Sosio-Legal di Komunitas Lokal Pedesaan Indonesia - Nurjanah, Binti Qoriatun; Abid, Ruston; Nafik, Moh (LPPM UNHASY, 2025)
The trend of child marriage in Indonesia remains high and is a chronic problem for the government and policymakers. The Indonesian government's commitment to addressing the issue of child marriage demonstrates political will by ratifying the Convention on the Rights of the Child through Presidential Decree No. 36 of 1990 and tightening the minimum age for marriage in Law No. 1 of 1974. Over the last decade, most researchers have focused on legal aspects and reproductive health. Several researchers have raised the issue of harmony, but it remains a general concept. An in-depth study of living law on how young couples negotiate “harmony” is important to complement the complexity of child and women's protection policies. This study aims to reveal the meaning behind the reality of underage couples in Sukomoro District, Nganjuk. The research approach employs a descriptive, qualitative approach, incorporating in-depth interviews with the actors. This study found that there is a “Maturity Myth,” in which the harmony displayed by couples is actually a camouflage to avoid the stigma of non-compliance with family norms. As a result, harmony becomes paradoxical, with the burden of independent domestic responsibilities. The researcher argues that contributors to disharmony are not only biological immaturity but also the failure of social roles in navigating the issue of child marriage and economic dependence. The results of this study provide an evaluation of the current marriage dispensation policy so that it considers not only administrative aspects but also the cognitive-social readiness of the couple.